Gas exchange and putrescine content as drought stress indicators in corn cultivars fertilized with silicon - Bianchini, Hudson Carvalho; Marques, Douglas Jose (Australian Journal of Crop Science, 2020)
The effects of drought stress on maize have been extensively reported in tropical and subtropical areas, including morphological changes in plants and reductions in the grain yield. The development of sustainable alternatives that help mitigate the negative impacts of water stress is indispensable for the development of agricultural crops. This study evaluates the effect of silicon fertilization in two irrigation blades, on gas exchange, putrescine content, quantification of Ca, K, Zn, and Fe by neutron activation and grain yield in two maize cultivars, tolerant and sensitive to drought stress. Two experiments were conducted, the first using BR-1010 (sensitive to drought stress) and the second using DKB-390 (tolerant to drought stress), in 19 dm-3 pots with one plant in each pot. The experiment was organized in randomized blocks, in a factorial scheme, combining two irrigation blades (30 percent and 100 percent of necessary water replacement) and two silicon conditions per pots: control (-Si), and 27g Si (+Si) using calcium silicate (10.5 percent Si) with four replicates. The contents of putrescine, Ca, K, Zn, and Fe, as well as transpiration rate, stomatal conductance, and net photosynthetic contents were quantified. Maize yield was measured at the end of the study. It was concluded that supplementation with Si contributes to a 12 percent increase in yield for BR-1010 (drought sensitive) and 14 percent for DKB-390 (drought tolerant). Si increased the net photosynthetic rate, transpiration rate, and stomatal conductance in DKB-390. The content of putrescine increased in plants submitted to drought stress and can be considered as an indicator of drought stress. The leaf contents of Ca, K, Zn, and Fe varied according to the cultivars and water blade studied.